TRADITIONAL MARKET VS DIGITAL MARKET: ADAPTATION IN SOCIAL INTERACTION AMONG GROCERY TRADERS - Hamdani; Jungjungan, Muhammad Arisandi; Irwansyah; Suharno, Muhammad Iqbal (Academic Solution Publisher, 2024)
This study aims to analyze the social adaptation strategies of traditional traders in Sukaramai Market, Medan in facing the development of the digital market. With a qualitative descriptive approach, this study explores how traditional traders interact and maintain the sustainability of their businesses amidst changes in people's consumption patterns that are more directed towards online shopping. Data were collected through interviews with 3 informants, namely 1 core informant (Grocery Trader) and 2 additional informants (Buyers), observation, and documentation. The results of the study show that traders in Sukaramai Market implement adaptation strategies, such as improving social relations with buyers, maintaining product quality, offering competitive prices, and maintaining business locations. However, the adoption of digital technology is still low due to limited knowledge and resources. This study highlights the importance of government support in helping traditional traders adapt to technology to strengthen the existence of traditional markets in the digital era.